ANALISIS KEGAGALAN PENALARAN KOVARIASIONAL MAHASISWA DALAM MENGONSTRUKSI GRAFIK FUNGSI - Yohanes, Barep; Darmawan, Puguh; Ikram, Muhammad (TRANSFORMASI, 2024)
This research aims to identify failures in covariational reasoning of mathematics education students in the Numerical Methods course. This research is descriptive qualitative type with the researcher as the main instrument and supporting instruments in the form of assignment sheets, interview guides and documentation. The research subjects were 18 students from the Mathematics Education study program, FMIPA, PGRI Banyuwangi University. The work results are grouped into 5 based on the type of function graph created, namely subjects without function graphs (4 students), graphing linear functions (5 students), graphing quadratic functions (6 students), graphing polynomial functions (1 student), and graphing circle functions (2 students). Covariational reasoning failures are identified based on the 5 mental actions that Carlos has compiled. The results showed that there was failure of mental action 1 in groups 1 subjects; 2nd mental failure in subjects groups 1 and 5; 3rd mental failure in subjects groups 1 and 4; 4th mental failure in subjects groups 1 subjects and 3, and mental failure 5 in subjects groups 1 and 2. Research can be continued by exploring aspects of the causes of failure in covariational reasoning.